Fucosylated chondroitin sulfate as a new oral antithrombotic agent - Fonseca, Roberto J. C.; Mourão, Paulo A. S. (Thrombosis and Haemostasis, 2006)
Fucosylated chondroitin sulfate is a potent anticoagulant polysaccharide extracted from sea cucumber. Its anticoagulant activity is attributed to the presence of sulfated fucose branches. We have shown that intravascular injection of fucosylated chondroitin sulfate inhibits thrombus formation in a venous and an arterial shunt model in rats. Since this compound resists digestion by enzymes that cleave mammalian glycosaminoglycans, we investigated the possibility that fucosylated chondroitin sulfate might be absorbed after oral administration. In fact, after oral administration of fucosylated chondroitin sulfate to rats, we observed a dose-dependent increase in the plasma anticoagulant activity, as assessed by assays for activated partial thromboplastin time (aPTT) and thrombin time (TT) (about 3-and 5-fold, respectively) and by anti-IIa activity. Furthermore, animals receiving daily oral doses of this glycosaminoglycan showeda decrease in thrombus weight on experimental models of venous and arterial shunt thrombosis. This antithrombotic action clearly has a strong relationship with anticoagulant activity. Similar doses of heparin administered orally had no effect on the plasma anticoagulant activity or on the thrombus weight. Finally, we observed that fucosylated chondroitin sulfate given orally to rats did not modify the bleeding time. Overall, our results indicate that fucosylated chondroitin sulfate is absorbed after oral administration and could become a promising oral anticoagulant.
Keywords: Glycosaminoglycans; fucosylated chondroitin sulfate; oral anticoagulants; heparin